Gambaran perilaku remaja tentang pencegahan kehamilan yang tidak diinginkan di sekolah menengah atas di Kota Manado - Siregar, Theodora; Porajow, Zwingly Christian Jefferson Gerard; Monintja, Tyrsa Christine Natalia (UNIVERSITAS SAM RATULANGI, 2025)
Background: Unintended pregnancy among adolescents remains a major public health concern both globally and in Indonesia. In Manado City, recent data on adolescent behaviour related to the prevention of unintended pregnancy are still limited. Aim: This study aimed to describe adolescent behaviour regarding the prevention of unintended pregnancy in senior high schools in Manado City. Methods: A quantitative descriptive study with a cross-sectional design was conducted. A total of 403 students were selected through cluster random sampling from two schools: SMA A and SMA B, Manado. Data were collected using a structured questionnaire that had been tested for validity and reliability (Cronbach’s alpha: knowledge = 0.931; attitude = 0.736). Data were analysed using univariate methods. Results: Overall, 76.2% of adolescents demonstrated good knowledge, 22.8% had sufficient knowledge, and 1.0% had poor knowledge regarding the prevention of unintended pregnancy. With respect to attitudes, 70.7% of respondents exhibited a positive attitude, while 29.3% showed a negative attitude. Conclusion: The majority of adolescents in Manado City possess good knowledge and hold positive attitudes toward the prevention of unintended pregnancy.